The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.4172/2471-9455.1000105
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic and Respiratory Measures as a Function of Age in the Male Voice

Abstract: The purpose of this study was to extend understanding of the effects of aging on the male voice by obtaining and analyzing both acoustic and respiratory measures across the aging continuum. Aerodynamic measurements such as vital capacity (VC), maximum phonation time (MPT) and the acoustic measurement Speaking Fundamental Frequency (SFF) are used commonly in Speech-language Pathology to aid in the assessment and treatment outcomes of vocal dysfunction. However, current research lacks analysis of the interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Regarding pitch, our observations were first consistent with a pattern in which speaking f0 decreases for both male and female speakers from young adulthood until middle age, except for the fact that the shoulder in this continuous decrease occurred at earlier ages in the present study (40 and 36 for male and female speakers, respectively) than typically reported in the literature, i.e., around ages 50-65 (Baken 2005;Bier et al 2017;Cox and Selent 2015). Second, we replicated the rise in speaking fundamental frequency expected from male speakers over 60, typically associated with vocal fold atrophy and histological changes (Harnsberger et al 2008;Torre and Barlow 2009;Dehqan and Scherer 2013), but not the fall for female speakers that-when observed-is associated with increased vocal fold mass due to edema, loss of muscle tone, ossification and/or hormonal changes (Kreiman and Sidtis 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Regarding pitch, our observations were first consistent with a pattern in which speaking f0 decreases for both male and female speakers from young adulthood until middle age, except for the fact that the shoulder in this continuous decrease occurred at earlier ages in the present study (40 and 36 for male and female speakers, respectively) than typically reported in the literature, i.e., around ages 50-65 (Baken 2005;Bier et al 2017;Cox and Selent 2015). Second, we replicated the rise in speaking fundamental frequency expected from male speakers over 60, typically associated with vocal fold atrophy and histological changes (Harnsberger et al 2008;Torre and Barlow 2009;Dehqan and Scherer 2013), but not the fall for female speakers that-when observed-is associated with increased vocal fold mass due to edema, loss of muscle tone, ossification and/or hormonal changes (Kreiman and Sidtis 2011).…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, the men had a trend of slight increases in f o between each of the age cohorts but the changes were not statistically significant. Previous studies reporting increased f o in men include: Cox and Selent, (2015)[43], Nishio and Niimi (2008)[44], along with three studies cited in Table 3. Previous studies reporting decreased f o in women include Nishio and Niimi (2008) [44] and several studies cited in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, several research studies have attempted to acoustically measure the aging analysis using cross-sectional data i.e. by comparing categories of age groups from young to elderly wherein the participants (speakers or the singers) differ in the age subgroups [10,22,17,23]. But the physiological differences among the participants can affect the measurement of age dependent impacts on acoustic parameters.…”
mentioning
confidence: 99%